The Deformation Behavior and Failure Modes of Surrounding Rock after Excavation: A Experimental Study - Jinping Liang; Haoyong Jing; Xiaorui Li; Gongyu Hou (Shock and Vibration)
The deformation and failure of the surrounding rock during roadway excavation often determine the choice of supporting methods. To study the deformation behavior and failure modes of the surrounding rock after excavation under unloading stress, structural model tests were carried out with a novel experimental device. The present structural model test using partial hollow thick-walled cylinder cement mortar specimen φ200 mm × 280 mm with a horizontal central circular hole of 60 mm diameter and the hollow height of 160 mm was conducted to investigate the deformation, failure characteristics, and AE response of a whole testing process from excavation to postunloading state. Experimental results revealed that the amount of deformation behind the surface is significantly higher than that in front of the surface, and the radial strain increases with the increase of the distance from the surface within the range affected by unloading. Furthermore, the unloading rate has a little effect on the radial deformation of the surrounding rock in front of the surface, but has a substantial effect on the radial deformation behind the excavation surface. The peak value of the strain rate at the unloading rate of 2 MPa/s is much higher than that at the unloading rate of 0.1 MPa/s. According to AE results and the failure of opening the boundary, the increase of unloading rate triggers and exacerbates the damage of the specimen under high in situ stress conditions. The surrounding rock expanded to the inner hollow, accompanied by large dilation and volume changes, and it resulted in the shrinkage of the hole diameter. A large number of rock slices are generated at the opening curved free surface and then fell off, whose morphology is similar to the rock blocks that fell off after caving failure and rock burst in situ field. The results show that the system can accurately simulate the mechanical response and acoustic emission response of the excavated surrounding rock, which provides a new experimental method for further study of the unloading response of the surrounding rock.